The correlation of ultimate analysis and calorific value on palm oil briquettes using durian seed adhesives. Issue 1 (March 2021) - Maulina, Seri; Sarah, M.; Misran, E.; Anita, M. F.
Abstract: Palm fronds are one of the wastes produced from oil palm plantations that have high potential and are suitable for use as raw material for biomass as renewable energy through carbonization and briquetting processes. Durian seeds contain amylose and amylopectin which can be used as an adhesive to improve the physical quality of the briquettes produced. Palm fronds are carbonized at 300°C for 90 minutes. The charcoal produced is mashed with a ball mill. The gluing process is carried out using an adhesive from durian seeds with a concentration of 5%, 15% and 25% with a char: adhesive ratio of 30:70, 50:50, and 70:30 and compressed at a pressure of 100 kg/m 2 . Ultimate analysis and calorific value are carried out to test the performance and quality of bio-charcoal briquettes.